The paradigm shift in allergy consultations through a digital ecosystem - Sánchez-Machín, Inmaculada; Poza-Guedes, Paloma; Mederos-Luis, Elena; González-Pérez, Ruperto (Frontiers in Digital Health, 2024)
In Spain, specialist outpatient care traditionally relied on in-person consultations at public hospitals, leading to long wait times and limited clinical analysis in appointment assignments. However, the emergence of Information and Communication Technologies (ICTs) has transformed patient care, creating a seamless healthcare ecosystem. At the Allergy Department, we aimed to share our experience in transitioning form a traditional linear model of patient flow across different healthcare levels to the implementation of a digital ecosystem. By telemedicine, we can prioritize individuals based on clinical relevance, promptly and efficiently addressing potentially life-threatening conditions such as severe uncontrolled asthma or hymenoptera venom anaphylaxis. Furthermore, our adoption of telephone consultations has markedly reduced the need for in-person hospital visits, while issues with unstable patients are swiftly addressed via WhatsApp. This innovative approach not only enhances efficiency but also facilitates the dissemination of personalized medical information through various channels, contributing to public awareness and education, particularly regarding allergies. Concerns related to confidentiality, data privacy, and the necessity for informed consent must thoroughly be addressed. Also, to ensure the success of ICT integration, it is imperative to focus on the quality of educational information, its efficient dissemination, and anticipate potential unforeseen consequences. Sharing experiences across diverse health frameworks and medical specialties becomes crucial in refining these processes, drawing insights from the collective experiences of others. This collaborative effort aims to contribute to the ongoing development of a more effective and sustainable healthcare system.